(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Sustainable healthcare systems require long-term strategies for disease prevention and health promotion. Despite the well-documented benefits of physical activity (PA), knowledge gaps persist among healthcare professionals regarding its clinical use. The Swedish handbook FYSS – Physical Activity in the Prevention and Treatment of Disease, addresses this gap by providing evidence-based PA recommendations for over 35 diagnoses, along with guidance on factors important for effective PA counselling. Primarily targeting healthcare providers, FYSS promotes sustainable, non-pharmacological treatment strategies and forms the scientific foundation for the Swedish Physical Activity on Prescription (FaR) method. The recent development of a digital version, eFYSS, represents an innovative step towards enhancing clinical applicability and supporting broader, more sustainable integration of PA in healthcare. Project Description: FYSS is developed by the Swedish Professional Associations for Physical Activity (YFA), with financial support from the Swedish National Board of Health and Welfare. Over 100 medical experts contributed to the fourth edition, FYSS 2021, which includes updated general and diagnosis-specific PA recommendations aligned with the latest evidence and public health goals. A standardised chapter format enhances usability in clinical practice. Nationally implemented as a core tool for prescribing FaR, FYSS is also integrated into health professional education programmes. To improve implementation, eFYSS was co-designed with healthcare professionals as a user-friendly digital platform providing rapid access to tailored PA recommendations during consultations. Dissemination efforts include national-level conferences, integration into medical curricula, and alignment with public health strategies. FYSS has also inspired international adaptations, including translations and versions used in the EU-funded EUPAP project. In 2025, a new initiative will launch a full digital version of FYSS in collaboration with the National Board of Health and Welfare, enabling lower environmental impact, continuous updates, and wider access. Conclusion: FYSS and eFYSS demonstrate how structured, evidence-based tools can integrate PA into routine healthcare. The digital format improves accessibility, scalability, and sustainability. Their use promotes equitable, non-pharmacological approaches to disease prevention and treatment, supporting national and global public health goals and offering a scalable model for other healthcare systems.